GE_GERICHTE P/8647/2020 vom 24. Juni 2024 - GE Cour de justice (2024)
QUALITÉ POUR RECOURIR;DÉNONCIATION CALOMNIEUSE;CLASSEMENT DE LA PROCÉDURE;DROIT D'ÊTRE ENTENDU | CPP.318.al2; CPP.319.al1.letb; CP.219; CP.303; CP.292